Čegec’s, Tarantino’s, and Zajec’s Pulp Fiction - BOBEK, Martina; GAJIN, Igor (Anafora, 2023)
This article explores multimediality and diversity in the poetry of Branko Čegec, the film Pulp Fiction by Quentin Tarantino, and the novel Soba za razbijanje by Tomislav Zajec. Their comparison is based on intermediality as the main feature of postmodernism, which provides a two-way or multi-way relationship between the analysed works, since each of them is already characterised by intermediality and citability. The main structural components are emphasised according to which the three works or multimedia texts, are intermedially similar, primarily through motifs and topics. The aim is to reveal Čegec’s intense intermedial sensitivity as an open dialogue of intermedial traces on both formal and stylistic, and subjective structures. A similar sensitivity to other media can be found in Tarantino’s film and Zajec’s novel. The article aims to determine the elements common to all three authors, that is, the three aspects of their emphasized intensity of thematic and presentational intermediality. Finally, the conception of their works will be placed in the context of postmodern creativity as a highly communicative intermedial state.